FOSTERING THE DIGITAL GENERATION: CHALLENGES IN HIGHER EDUCATION INSTITUTIONS DURING THE FOURTH INDUSTRIAL REVOLUTION (IR4.0) EDUCATIONAL LANDSCAPE - Mohd Kamal Mohd Shah; Muhammad Huzaifah Mohd Kamal; Mohd Ashraf Che Soh; Jahidih Saili; Qamarul Hafiz Jaafar; Irma Wani Othman (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This paper deliberates on the construction of the digital generation in contemporary times across various aspects of life, emphasizing the imperative for concerted efforts to advance the nation’s capabilities for competitive positioning on the global stage. The research objectives explore the role of Higher Education Institutions (HEIs) in fostering digital technology advancements. Steps toward digital technology progression necessitate interventions such as prioritizing technology-centric courses for students. Discussed issues encompass (i) the role of HEIs in advancing technology, (ii) the significance of digital technology utilization, (iii) the impact of digital technology development among students, and (iv) factors influencing the rapid evolution of technology in tandem with the pace of the era. Data for the study were gathered from diverse sources, including research findings in journals, scholarly writings, online news sources, public forums, and reference books. The study successfully identifies means through which the digital generation can be nurtured, guiding them through appropriate channels to discern the positive and negative ramifications of digital revolution actions in the present generation. The use of digital technology holds potential benefits for users, enhancing individual knowledge and fostering critical thinking skills. The application of digital technology can significantly impact the technological development among graduates, empowering them with digital proficiency. These skills prove invaluable in employment pursuits, given the ubiquitous incorporation of digital technology across various professions today. The rapid technological advancements driven by factors such as high curiosity towards technology have led the younger generation to explore and employ various digital tools, such as smartphones. Amidst efforts to cultivate the digital generation, challenges emerge, with one prominent issue being the misuse of digital technology. Study findings reveal that various initiatives, particularly governmental efforts, have been undertaken to address digital technology misuse, contributing to cybercrimes and online fraud. Consequently, societal perceptions towards digital technology have become increasingly negative. These challenges impede governmental endeavors to foster a digital generation. Thus, in alignment with the identified issues, this study underscores the shared responsibility of all stakeholders in realizing the nation’s vision to produce an advanced digital generation in the present era.